ISLAM DAN MUAMALAH - A. Rahma Febriana; Hasriah Hasriah; Intan Junaeda; Nirmayani Tiala; Nurasmin Nurasmin (STKIP Subang, 2025)
ABSTRACT This paper aims to provide a comprehensive understanding of the concept of Muamalah within the perspective of Islamic law. Etymologically, Muamalah means interaction, while terminologically it refers to all rules and activities in socio-economic life regulated by Islamic law to achieve mutual benefit. The study explains the broad scope of Muamalah, covering economic activities such as buying and selling (bai’), leasing (ijarah), and partnerships (syirkah), as well as social deeds like zakat and waqf. Fundamental principles include permissibility (ibahah), justice, mutual consent (taradhi), honesty, and transparency. The paper emphasizes the strict prohibition of practices like riba (usury), gharar (uncertainty), and maisir (gambling), as regulated by the Qur'an and Hadith. The application of Muamalah is intended to create economic justice, protect rights, and bring blessings in wealth Keywords: Muamalah 1, Islamic Law 2, Islamic Economics 3 ABSTRAK Artikel ini bertujuan untuk memberikan pemahaman komprehensif mengenai konsep Muamalah dalam perspektif hukum Islam. Secara etimologis, Muamalah berarti saling berinteraksi, sedangkan secara terminologis mengacu pada segala aturan dan aktivitas kehidupan sosial-ekonomi yang diatur oleh hukum Islam demi mencapai kemaslahatan bersama. Kajian ini menjelaskan ruang lingkup Muamalah yang luas, meliputi aktivitas ekonomi seperti jual beli (bai’), sewa-menyewa (ijarah), dan kerja sama (syirkah), serta perbuatan sosial seperti zakat dan wakaf. Prinsip-prinsip dasarnya mencakup kebolehan (ibahah), keadilan, kerelaan (taradhi), kejujuran, dan transparansi. Artikel ini menekankan larangan ketat terhadap praktik seperti riba, gharar (ketidakjelasan), dan maisir (judi), yang diatur secara tegas dalam Al-Qur'an dan Hadis. Penerapan Muamalah bertujuan menciptakan keadilan ekonomi, melindungi hak-hak, dan mendatangkan keberkahan dalam harta. Kata Kunci: Muamalah 1, Hukum Islam 2, Ekonomi Syariah 3